2021
DOI: 10.3390/ijms22073296
|View full text |Cite
|
Sign up to set email alerts
|

Selective Activation of CNS and Reference PPARGC1A Promoters Is Associated with Distinct Gene Programs Relevant for Neurodegenerative Diseases

Abstract: The transcriptional regulator peroxisome proliferator activated receptor gamma coactivator 1A (PGC-1α), encoded by PPARGC1A, has been linked to neurodegenerative diseases. Recently discovered CNS-specific PPARGC1A transcripts are initiated far upstream of the reference promoter, spliced to exon 2 of the reference gene, and are more abundant than reference gene transcripts in post-mortem human brain samples. The proteins translated from the CNS and reference transcripts differ only at their N-terminal regions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 110 publications
(139 reference statements)
0
10
0
Order By: Relevance
“…Much of the versatility of this co-regulator in its tissue-specific roles can be ascribed to its multiple tissue-specific mRNA isoforms and corresponding protein isoforms. PGC-1α protein isoforms differ in biochemical properties, protein-protein interactions, stability, and subcellular localization [ 46 , 47 , 48 , 49 ]. Isoform formation depends partly on the choice of one of the following promoters for transcription initiation: the proximal (Prox) promoter (encoding the canonical 797-aa PGC-1α1), the 14-kb upstream alternate (Alt) promoter, the downstream liver-associated promoter, and a ~0.6-Mb upstream brain-associated promoter (distal promoter) ( Figure 7 A and Figure S7 ) [ 43 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Much of the versatility of this co-regulator in its tissue-specific roles can be ascribed to its multiple tissue-specific mRNA isoforms and corresponding protein isoforms. PGC-1α protein isoforms differ in biochemical properties, protein-protein interactions, stability, and subcellular localization [ 46 , 47 , 48 , 49 ]. Isoform formation depends partly on the choice of one of the following promoters for transcription initiation: the proximal (Prox) promoter (encoding the canonical 797-aa PGC-1α1), the 14-kb upstream alternate (Alt) promoter, the downstream liver-associated promoter, and a ~0.6-Mb upstream brain-associated promoter (distal promoter) ( Figure 7 A and Figure S7 ) [ 43 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…A new promoter of PGC-1α was identified and it is localized far upstream of the reference promoter of the PGC-1α gene [ 26 ] ( Figure 1 ). This promoter initiates CNS-specific transcripts of PGC-1α, which differ from the reference gene transcript in N-terminus sequence and contain novel exons B1-B5 spliced to exon 2 of the reference gene [ 26 , 27 ]. These transcripts encode two full-length and several truncated isoforms of PGC-1α [ 26 ].…”
Section: Cns-specific Isoforms Of Pgc-1αmentioning
confidence: 99%
“…Activation of the CNS-specific PGC-1α promoter by Forkhead Box A2 (FOXA2), a transcription factor vital for differentiation and functioning of dopaminergic midbrain neurons but not the reference gene promoter in SH-SY5Y cells, indicates involvement of CNS-specific transcripts in the generation and maintenance of dopaminergic neurons [ 30 ]. It was shown that activation of CNS-specific PGC-1α promoter affected the expression of ALS and Parkinson’s disease risk genes in SH-SY5Y cells [ 27 ]. Still, the role of these isoforms in the functioning of the CNS or the pathophysiology of neurodegenerative diseases in vivo remains to be elucidated; therefore, it is too early to target them in therapies.…”
Section: Cns-specific Isoforms Of Pgc-1αmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Cas9 nuclease can be converted into an RNA-guided DNA-binding protein (dCas9) and then fused to transcription activation or repressor domains. These dCas9-activator fusions target the promoter/enhancer regions of endogenous genes to modulate gene expression [ 160 , 161 ].…”
Section: Genome Editing Technologies For “Quantum-leap” Improvements In Yield-limited Crops Are Ready But Where Are the Targets?mentioning
confidence: 99%